A prospective study of the incidence and outcomes of eclampsia in a tertiary care hospital and teaching institute in India - Gandhi, Garima; Chandnani, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is a common cause of maternal and foetal morbidity and mortality in India and the rest of the world accounting for nearly 10% of all maternal deaths. However, there is a relative scarcity of outcome data for patients with eclampsia in India. Our goal was to estimate the incidence of eclampsia, the maternal and foetal outcomes of patients presenting with eclampsia, and predictors of clinical outcomes in these patients. Objective of this study was to estimate the incidence of eclampsia in patients who delivered at a single tertiary care institution over a 2-year period and to study the maternal and perinatal outcomes in those patients. Methods: Prospective cohort study conducted from September 2008 to August 2010 on all patients with eclampsia admitted during the study period at Lok Nayak Hospital, New Delhi, India. Results: The incidence of eclampsia among total deliveries was 0.45%. About 97% of these patients received parenteral magnesium sulphate as the primary anticonvulsant therapy. Caesarean section was performed in 22.7% and majorities were done for foetal distress. Maternal complications were encountered among 17% of patients. There were 2 maternal deaths (2.3%), 13 stillbirths (14.1%) and 7 early neonatal deaths (7.9%). Conclusions: The incidence of eclampsia among all deliveries over a 2-year period at a tertiary care centre in India was 0.45%. Parenteral magnesium sulphate was effective in the vast majority of these patients in controlling the seizures. Further studies to evaluate whether early registration for antepartum care improves maternal and foetal outcomes in patients with eclampsia are warranted.